FORMATION OF ETHNO-CULTURAL COMPETENCE OF STUDENTS, THE FUTURE SPECIALISTS OF KAZAKHSTAN (Journal of Educational Sciences, 2018)
This article discloses the concept of “Ethno-cultural education”. The modern world is characterizedby the growing processes of globalization. However, along with this, there is a clear tendencytowards national-cultural identification, aspiration of the people to preserve their identity and uniqueness.In world science, this phenomenon is seen as an ethnic renaissance, putting forward new demandsfor education. The article reveals the tasks and principles of ethnocultural education. The tasksinclude the formation of cultural values of people living on the territory of Kazakhstan, positive valueorientations of the development of the culture of Kazakhstan, the formation of a culture of interethniccommunication. The principles include: openness and respect for the national traditions of the peoplesof Kazakhstan, the values of the Kazakh people, readiness for the dialogue, etc. The article concludeswith practical recommendations on the formation of the ethno-cultural competence of Kazakhstan’sfuture specialists.Ethno-oriented forms of extracurricular work with students include: 1) socially-oriented forms(“round tables”, conferences, meetings with representatives of various ethnic diasporas, historians, ethnographers,cultural figures, celebration of memorable dates of historical significance, anniversaries ofoutstanding figures of culture, literature, science and folk heroes); 2) cognitive forms (local history andethnographic excursions, hiking, cultural days and festivals, oral journals, quizzes, theme nights, museumactivities, exhibitions); 3) practice-oriented forms (trainings, organizational and activity games); 4)entertainment forms (evening events, public holidays, “Hangouts”, “Fair”, folklore concerts and theaterperformances, competitions in national sports and folk games, competitions for connoisseurs of folkcustoms, national cuisine, traditional crafts, etc).Key words: students, future specialist, personality development, culture, interaction of cultures,ethno-cultural competence, ethnos.